Shade Avoidance - Casal, Jorge José (2012)
The presence of neighboring vegetation modifies the light environment experienced by plants, generating signals that are perceived by phytochromes and cryptochromes. These signals cause large changes in plant body form and function, including enhanced growth of the hypocotyl and petioles, a more erect position of the leaves and early flowering in Arabidopsis thaliana. Collectively, these so-called shade-avoidance responses tend to reduce the degree of current or future shade by neighbors. Shade light signals increase the abundance of PHYTOCHROME INTERACTING FACTOR 4 (PIF4) and PIF5 proteins, promote the synthesis and redirection of auxin, favor the degradation of DELLA proteins and increase the expression of auxin, gibberellins and brassinosteroid-promoted genes, among other events downstream the photoreceptors. Selectively disrupting these events by genetic or pharmacological approaches affects shade-avoidance responses with an intensity that depends on the developmental context and the environment. Shade-avoidance responses provide a model to investigate the signaling networks used by plants to take advantage of the cues provided by the environment to adjust to the challenges imposed by the environment itself.